Analisis Gaya Bahasa Perulangan pada Lirik Lagu dalam Album Monokrom Karya Tulus dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia di SMA - Rina Rosdiana; Ega Septiani Putri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, UNPAK, 2021)
Language is very close to human life because language is able to convey a message through spoken words, especially in song lyrics that have the same characteristics as poetry, this is certainly contains a diverse language style. This study aims to find out the use of language styles on song lyrics in a monochrome album of Tulus. Not only about that, this also aims to know the implications of using language styles in learning Indonesian in Senior high school. The writer uses qualitative descriptive method in this research techniques that refers to the theories of the experts. The research data used in conducting the research is to use excerpts the lyrics of song containing repetitive language styles such as simploke, chiasm, epizeukis and anaphora. Moreover, the data that has been collected will be analyzed and described. The result of the language styles analysis in the lyrics of the song are found 68 quotes, including simploke 13, chiasmus 39, epizeukis 6, and anafora 8. The results of this study can be used as teaching material innovation in Indonesian language learning in senior high school because the language styles materials are learned by the senior high school students. The use of repetitive language styles has an important connection to suppressing meaning, so students are able to express their message. However, from 10 songs on the monochrome album, it can be concluded that the song has more chiasm. Chiasm is a style of language in which there are two different words but it can have the same or different meaning.